2013
DOI: 10.1038/gene.2013.42
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation near IRF8 is associated with serologic and cytokine profiles in systemic lupus erythematosus and multiple sclerosis

Abstract: Alleles of IRF8 are associated with susceptibility to both systemic lupus erythematosus (SLE) and multiple sclerosis (MS). While high type I interferon (IFN) is thought to be causal in SLE, type I IFN is used as a therapy in MS. We investigated whether IRF8 alleles were associated with type I IFN levels or serologic profiles in SLE and MS. Alleles which have been previously associated with SLE or MS were genotyped in SLE and MS patients. The MS-associated rs17445836G allele was associated with anti-dsDNA autoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 41 publications
2
46
1
Order By: Relevance
“…IRF8 is highly expressed in mouse and human GCs (15,30) and shares a large number of common target genes in GC B cells, about half of which are also targeted by PU.1 (16). IRF8 has also been implicated in the development of B cell-driven systemic autoimmune diseases in humans and mice (31,32). Finally, several recent studies have identified roles for IRF8 in the pathogenesis of human diffuse large B cell lymphoma (33,34) and probably mouse diffuse large B cell lymphoma as well (15).…”
Section: Discussionmentioning
confidence: 99%
“…IRF8 is highly expressed in mouse and human GCs (15,30) and shares a large number of common target genes in GC B cells, about half of which are also targeted by PU.1 (16). IRF8 has also been implicated in the development of B cell-driven systemic autoimmune diseases in humans and mice (31,32). Finally, several recent studies have identified roles for IRF8 in the pathogenesis of human diffuse large B cell lymphoma (33,34) and probably mouse diffuse large B cell lymphoma as well (15).…”
Section: Discussionmentioning
confidence: 99%
“…Follow up studies have demonstrated examples of polymorphisms which are associated with higher circulating levels of type I IFN, such as IRF5, IRF7, SPP1, and others 12, 34, 35 . Examples of polymorphisms that result in increased IFN-induced gene expression or increased sensitivity to interferon have been demonstrated, such as STAT4, IFIH1, and IRF8 3638 .…”
Section: Type I Interferon: Pathogenic Immune System Phenotype Regulamentioning
confidence: 99%
“…The same STAT4 variant has been associated with dsDNA autoantibodies, as well as increased sensitivity to type I IFN 37, 42 . A number of SLE-risk loci have been associated with autoantibody formation in SLE, including STAT4 and IRF5 as mentioned above, IRF7, IRF8, UBE2L3, CR2, and others 35, 38, 44, 45 . While the exact molecular mechanism by which these genetic variants influence autoantibody formation is not clear, it is interesting that many of these genes have functions within the TLR and type I IFN pathways.…”
Section: Associations With Autoantibodies and Nephritismentioning
confidence: 99%
“…One likely factor is intrinsic over-activity within the TLR signaling system. Human genetic variants in IRF5, IRF7, and IRF8 have been implicated in SLE susceptibility 29-36 , suggesting that gain-of-function polymorphisms in these molecules augment TLR signaling. Many studies have placed the IRF family as central mediators in human SLE 37 .…”
Section: Introductionmentioning
confidence: 99%